Navigating uncharted waters: Developing a standardized approach for evaluating and implementing biosimilar products at a comprehensive cancer center. (8th December 2020) - Villanueva, Mara N; Davis, Jennifer E; Sobocinski, Stacey M
Abstract: Purpose: The processes for formulary implementation and electronic health record (EHR) integration of biosimilar products at a comprehensive cancer center are described. Implications for research protocols are also discussed. Summary: The existing literature focuses on practical considerations for formulary addition of biosimilar products, but there is a lack of guidance on how to implement the change, particularly within the EHR. Before building the ordering tools for biosimilars, the clinical and informatics teams should determine the role of biosimilars at the institution, identify drug-specific product characteristics that affect medication build, and characterize implications of future formulary changes or drug shortages. Leveraging an orderable record provides the ability to include logic that maps to multiple products and also allows for future implementation of changes within the medication record rather than requiring "swaps" at the treatment protocol level. The institutional review board should coordinate changes in affected research protocols and consent forms and work with principal investigators to amend protocols when necessary. Pharmacy leaders should develop processes to oversee inventory during the transition period and minimize the risk of errors. Conclusion: The development of a standardized approach for evaluating and implementing biosimilar products improves efficiency and collaboration among the various team members responsible for the products' integration into existing workflows, including implications for clinical research. Implementing biosimilars for agents used to treat cancer will pose new challenges and require additional considerations. Partial implementation of biosimilars continues to pose multiple challenges in the provision of patient care.